Improvement of technical means for recycling of technogenic waste to construction fiber. (June 2022) - Klyuev, Sergey; Sevostyanov, Vladimir; Sevostyanov, Maxim; Fediuk, Roman; Sabitov, Linar; Ageeva, Marina; Fomina, Ekaterina; Klyuev, Alexander; Protsenko, Anastasia; Goryagin, Pavel; Babukov, Vladimir; Shamgulov, Roman
Abstract: Currently, a very significant environmental problem is the increase in the accumulation of solid domestic and industrial waste, including the polymer composition. There is a need to involve these wastes in processing, including in the production of building materials. On this way, the issue of reducing the energy intensity of grinding technogenic polymeric materials is relevant. For the secondary use of technogenic fibrous waste in construction, it is necessary to use special technological mechanisms that are not currently available. To fill this gap, an apparatus with a multi-link working body was developed, which was the objective of this article. The optimal technical characteristics of the apparatus were determined when modeling the process of complex processing of technogenic fibrous materials with sizes of single pieces of 30–100 mm dimensions of the working chamber L × B × H = (420 × 350 × 400) · 10 -3 m, maximum dimensions of the screening openings of the chain cloth l = (20 × 25) · 10 -3 m; frequency of rotation of the output shaft of the motor-reducer n = 50–600 rpm; oscillation amplitude of the drive link А = (50–60) · 10 -3 m; electric motor power N = 1.1 kW; working length of elements for the intensification of the working process of cutting 50 · 10 -3 m; needle 70 · 10 -3 m; unit weight m = 55 kg. The technological capabilities of the developed apparatus were established: active movement of material in the working space, high screening capacity, creation of complex spatial shear deformation of the material being processed, the implementation of the self-cleaning effect, a developed working surface, the possibility of removing waste inclusions from the technogenic charge during processing.